Structural and optical properties of evaporated Ge/Al Bilayer thin films - El-Nasser, H.; Yakuphanoğlu, Fahrettin; Mahasneh, A.; Ahmad, A. (Unimap Press, 2011)
Germanium- aluminum (a-Ge/Al) bilayer thin films with two different Al thicknesses were deposited onto glass substrates by thermal evaporation technique. The structural and optical properties were investigated and the effect of Al layer thickness on film properties was discussed. X-ray diffraction (XRD) confirmed the amorphous nature of the films under study. The small values of the roughness (7.04 nm, 7,2 nm) obtained from atomic force microscopy (AFM) measurements show relatively smooth surfaces, The optical properties of aGe-Al bilayer thin films were determined from the analysis of measured spectroscopic ellipsometry over the wavelength range 300-1000 nm at room temperature. The refractive index, extinction coefficient and thicknesses were obtained by the analysis of the ellipsometric spectra through Cauchy, and the Taue-Lorenz models, have been calculated. The optical energy gap was estimated from the absorption coefficient values which were estimated from the absorption coefficient values using Tauc's procedure Our results show that the optical band gap decreases with increasing Al layer thickness.
Keywords: Optical properties; Spectroscopic ellipsometty; Ge/Al bilayer thin films